Infection prevention in endoscopy practice: comparative evaluation of re-usable vs single-use endoscopic valves. Issue 2 (June 2021) - Pasquale, L.; Maurano, A.; Cengia, G.; Da Massa Carrara, P.; Germanà, B.; Graziani, M.G.; Manes, G.; Pisani, A.; Golia, M.; Marciano, E.; Rodella, L.; Schiffino, L.; et al.
Summary: Re-usable air/water and suction valves used in endoscopes often demonstrate risk of infection. To the authors' knowledge, the safety and efficacy of re-usable and single-use valves have not been compared to date. As such, a laboratory investigation was undertaken to compare the safety and efficacy of re-usable and single-use valves at 11 Italian endoscopy sites. Safety was evaluated by analysing the rinse liquid of reprocessed re-usable valves ready for use, and efficacy was assessed based on the completion of endoscopic procedures without valve malfunction. This study found significantly lower contamination of single-use valves compared with re-usable valves (0 vs 29.1%, respectively; P =0.007) and similar efficacy (97.6 vs 98.8%, respectively; P =ns). Microbiological analysis of the rinse liquid of reprocessed re-usable valves identified various surviving micro-organisms and highlighted their potential pathogenicity. Such data suggest that sterile single-use valves may be safer than re-usable valves, and have comparable performance.